Juvenile Black-legged Kittiwakes Rissa tridactyla with deformed bills and clubfeet in the Barents Sea - Kylin, Henrik (Ornis Svecica, 2005)
Juvenile Black-legged Kittiwakes Rissa tridactyla with deformed bills and feet were observed in the Barents Sea in 1996, first while passing between Franz Josef Land and Novaya Zemlya on 21–24 July (at least 10 birds) and then off the West Coast of Svalbard 20–21 September (at least 2 birds). Deformities were manifest as prolonged upper or lower mandible, hooked or crocked upper mandible, crossed bill and clubfeet. This paper reports the circumstances of the observations and discusses possible causes. Among the possible causes are nutritional deficiencies, epizootic events, environmental pollutants (persistent organic pollutants, heavy metals or radioactivity), or combinations of these.